Against the Holistic Temptations: A Critique of Three Related Fictions in Constitutional Theory. (3rd July 2018) - Zhang, Qianfan
Abstract : This article provides an analytical critique of three related concepts: Rousseau's general will, Sieyes's constituent power, and Carl Schmitt's political unity and political decision, with a reference to the catastrophic constitution-making practice in Venezuela. The constituent power has become a supreme power beyond every institutional control and the constitution-making body is justified in representing the "political unity" to reach "fundamental political decision", ultimately because they are supposed to represent the "general will" that has never existed in the real world. Rousseau's sacrosanct "general will" is a fiction constructed by his holistic methodology, but has been erroneously transformed into reality to guide the constitutional and legislative practices. In the real world, of course, the so-called "general will" is no more than the will of the majority which, like the will of minorities, is prone to err in its judgments, only that the probability of the majority's error is lower under certain conditions. Once removed of the false halo of the never-erring general will, the constituent power represents merely the will of the majority, while a political unity can never achieve absolute unity, and dissent opinions are the necessarily part of a normal society and shall always be given the opportunity to prove itself. The evil genie of absolute power shall be put back to and sealed in the Pandora's Box, to which it properly belongs.